Public Relations Strategy for Saka FM Community Radio in Maintaining Existence as a Da’wa Media - Saada, Siti (Journal of Islamic Communication and Counseling, 2023)
The existence of the public relations function eases an institution to establish good relations with the community. The role of public relations in an institution is needed to maintain its existence, both in government and private institutions. Therefore, this study aims to determine the role of private-public relations in maintaining its existence. In particular, this study describes the strategy the Saka FM community radio public relations carried out to maintain its existence as a da’wa media. This research used a qualitative approach and was carried out on the Saka FM community radio under the auspices of the Gedhe Kauman Mosque. The determination of informants was designated through the purposive technique, while the data collection was through observation, in-depth interviews, and documentation. This research uses the Niche theory, which states that a media’s founding pillar is divided into capital, content, and audience types. The results showed that Saka radio could stand on its own based on the Niche theory. The Saka FM radio public relations strategy has not fulfilled its ideal function as a community radio. Nevertheless, Saka FM radio has maintained its existence as a da’wa media through its marketing department.